The human Piwi protein Hiwi2 associates with tRNA-derived piRNAs in somatic cells. Issue 14 (18th July 2014) - Keam, Simon P.; Young, Paul E.; McCorkindale, Alexandra L.; Dang, Thurston H.Y.; Clancy, Jennifer L.; Humphreys, David T.; Preiss, Thomas; Hutvagner, Gyorgy; Martin, David I.K.; Cropley, Jennifer E.; Suter, Catherine M.
Abstract: The Piwi-piRNA pathway is active in animal germ cells where its functions are required for germ cell maintenance and gamete differentiation. Piwi proteins and piRNAs have been detected outside germline tissue in multiple phyla, but activity of the pathway in mammalian somatic cells has been little explored. In particular, Piwi expression has been observed in cancer cells, but nothing is known about the piRNA partners or the function of the system in these cells. We have surveyed the expression of the three human Piwi genes, Hiwi, Hili and Hiwi2, in multiple normal tissues and cancer cell lines. We find that Hiwi2 is ubiquitously expressed; in cancer cells the protein is largely restricted to the cytoplasm and is associated with translating ribosomes. Immunoprecipitation of Hiwi2 from MDAMB231 cancer cells enriches for piRNAs that are predominantly derived from processed tRNAs and expressed genes, species which can also be found in adult human testis. Our studies indicate that a Piwi-piRNA pathway is present in human somatic cells, with an uncharacterised function linked to translation. Taking this evidence together with evidence from primitive organisms, we propose that this somatic function of the pathway predates the germline functions of the pathway in modern animals.